Research Problem Component in the MA Theses of Kurdish Poetry (2003-2010) at Salahaddin University - Kawa Ali Mardan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study entitled "Research Problem Component in the MA theses of Kurdish Poetry (2003-2010) at Salahaddin University" Is an attempt to make the process of research writing in the field of Kurdish poetry more academic in academic theses. In this study, one of the essential components of academic research has been highlighted; the role and effectiveness of this component in the academic studies has been demonstrated. It is obvious that this component is one of the significant poles of the academic research and the basis of other component and elements of research is built on it. From this viewpoint, this subject is taken into account and analyzed carefully on the MA Kurdish poetry theses in order to show this component in MA theses, to what extent it has been able to be used scientifically and properly. In this regard, they have been evaluated by scientific criteria for the way research are dealt; so that they will be scientifically shown and the way of dealing. For this purpose, in this study, descriptive and analytical methods have been utilized, based on the established principles of academic research. In the findings of this study, it generally seems that the academic MA theses on Kurdish poetry have not taken methodological procedures in articulating their research problems.